Corporate finance in Brazil: evidence on bank lines of credit - Liu, Susana Xue (2016)
This article represents one of the first empirical examinations of the use of bank lines of credit among Brazilian public and private firms, and finds that lines of credit is a large and important source of corporate finance in Brazilian economy (86,6 % of firm-years have a line of credit between 2011 and 2015), but it only represents a tiny portion of total assets. Moreover, the majority of lines of credit are short-term (within 1 year). The principal finding of the articles is that, different from the advanced US and Europe credit market, the EBITDA accounting-based covenant is not prevalent in Brazil. Furthermore, using database of a local Brazilian bank, this is the first paper that proves the cash theory, the relationship-based banking and lending, and the liquidity insurance theory at the same time. I find that younger and larger firms are more likely to use lines of credit. Additionally, older and smaller firms with less tangible assets and less capital expenditure tend to rely more on credit lines than cash in liquidity management.